Interventions Post Catheter Removal (iPCaRe) in the Acute Care Setting: An Evidence- and Consensus-Based Algorithm. Issue 6 (November 2020) - Gray, Mikel; Beeson, Terrie; Kent, Dea; Mackey, Dianne; McNichol, Laurie; Thompson, Donna L.; Engberg, Sandra
Abstract : Despite advances in the prevention of catheter-acquired urinary tract infections achieved by programs that include removal of the indwelling urinary catheter at the earliest possible time, evidence guiding bladder and incontinence management strategies following discontinuation of a catheter is sparse. To address this gap and guide best practice, the WOCN Society appointed a Task Force to develop an evidence- and consensus-based algorithm guiding clinical decision-making for effective bladder and incontinence management strategies after indwelling urinary catheter removal. This article describes the design and development of the algorithm, consensus-based statements used to guide best practice in this area, and its content validation.